GAMBARAN STATUS GIZI PADA SISWA SEKOLAH DASAR KECAMATAN SIAK KECIL KABUPATEN BENGKALIS - Ira Widya Jahri; Suyanto "; Yanti Ernalia (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTNutrition is one of the indicators to assess the health of a country's development success in building quality human resources. Less nutrition in school children can cause delays in physical growth and motor development, lower IQ, behavioral disorders, lack of social skills and susceptibility to infectious disease. The purpose of this study is to describe the nutritional status of primary school children in Siak Kecil Bengkalis. This research is a descriptive study with cross-sectional design. The subject in this reseacrh were 350 students from grade 1 – 6 were taken with random sampling technique. Data were collected by questionnaire filled out by parent respondents to assess student characteristics data and calculate BMI by measuring weight and height to get the nutritional status of students. Nutritional status is divided into malnutrition, underweight, normal, overweight, and obesity based on standard anthropometric indicators BMI per age. The data showed that children with malnutrition were 6 children (1,7%), underweight were 42 children (12,0%), normal were 266 children (76,0%), overweight were 20 children (5,7%), and obesity were 16 children(4,6%).Keywords: elementary school students, nutrition, nutritional status